P-225 YI Development of Care Pathway for Initiation of Enteral Nutrition Therapy for Pediatric Crohns Disease—Single Center Quality Improvement Initiative. (February 2017) - Mansoor, Sana; Costantino, Jaclyn; Molle-Rios, Zarela
Abstract : Background: The role of enteral nutrition (EN) therapy is well established in treatment of mild-moderate pediatric Crohn's disease (CD). Recent trends suggest increasing interest in use of EN therapy in pediatric IBD centers across US including our institution where we aim to make this treatment modality popular amongst providers and families. Reasons for underutilization include lack of comfort amongst providers in prescribing EN due to absence of a standardized protocol, delayed delivery of formula and supplies, and need for admission to the hospital to provide education on nasogastric (NG) tube feeds. Latter is an added burden to families due to which they often forgo the option of EN therapy if child fails to drink formula by mouth. Methods: Our quality improvement initiative focuses on developing an institution wide protocol for induction and maintenance treatment using exclusive or partial enteral nutrition (EEN/PEN) therapy for pediatric CD. Induction phase consists of administration of a polymeric formula (PO/NG) to meet 80% to 100% caloric requirements. Close follow-up with the GI provider and registered dietician (RD) is provided via monthly office visits and a secure patient portal. If clinical remission is achieved in 8 to 12 weeks after initiation of EN therapy, then maintenance therapy is offered to families comprising of goals to meet 50% caloric needs via EN and 50% via regular food. Additional therapies will be considered if clinically significant improvement is not achieved at 4 to 6 weeks follow-up. For patients planned to receive EN via NG tube, some initiatives include providing families with standardized educational videos onKidshealth.org to view at home, meeting with dedicated RDs, getting insurance authorization for supplies and setting up nursing-led education sessions in our outpatient unit which will also coordinate with visits from the representatives of durable medical equipment companies. We also have standardized orders in the electronic medical records to initiate tube feedings and discharge instructions. We conducted a lecture for all providers and nurses from the outpatient unit to educate on the new protocol. These care pathways are now displayed in our outpatient GI clinics. For patients electing to take EN by mouth, we have a smart form with the amount of formula required by age and gender to be able to initiate therapy the same day of the office visit in case the RD is not available. Results: Since 2015 only 10 patients with CD were prescribed EN therapy. Seven patients completed the induction successfully with mean duration of 10.9 (±6.4) weeks. Mean BMI before and after induction was 16.1 (±2.7) and 17.0 (±2.6). Markers of clinical remission after EN induction included reduction in CRP (6.1 7.0–0.85 ±0.6) and ESR (27.8 ± 30.2–22.2 ± 28) along with increased albumin (3.3 ± 0.7–3.8 ± 0.3). We could not calculate P -values for statistical significance due to small cohort of patients. Conclusions: We hope that by providing a standardized EN therapy protocol, educating families and facilitating provision of supplies, we can increase comfort level of our providers in prescribing EN therapy and make it a more acceptable modality of treatment for mild-moderate CD at our institution.